Facile Synthesis of N-Substituted 4-Amino-6-methyl Resorcinols from Polysubstituted Cyclohexanone - Tang, Ruotian; Jiang, Chunfeng; Li, Hongliang; Li, Wei; Xu, Youjun (Synlett, 2017)
A novel synthesis of N-substituted 4-​amino-​6-​methyl resorcinols from polysubstituted cyclohexanone was developed. The reaction was performed in an easy ‘one-pot’, tandem manner with well-tolerated substituent on the nitrogen to give the desired compound in good to excellent yield. This highly efficient method will find broad application in the synthesis of some natural products and bioactive interesting compounds.
Keywords: amino resorcinol; tandem process; aromatization; voglibose; carbasugar